2018
DOI: 10.1002/cbic.201800651
|View full text |Cite
|
Sign up to set email alerts
|

Photoinducible Oncometabolite Detection

Abstract: Dysregulated metabolism can fuel cancer by altering the production of bioenergetic building blocks and directly stimulating oncogenic gene‐expression programs. However, relatively few optical methods for the direct study of metabolites in cells exist. To address this need and facilitate new approaches to cancer treatment and diagnosis, herein we report an optimized chemical approach to detect the oncometabolite fumarate. Our strategy employs diaryl tetrazoles as cell‐permeable photoinducible precursors to nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Comparative metabolomic analyses of these different models, and the development of improved tools to assess subcellular metabolite levels should aid in the future definition of this phenomenon. [37][38] An ancillary insight from our analysis is the distinct information available from studying the consequences of FH rescue (as was done in this study) versus studying the conditions of FHdependent transformation. For example, our whole proteome analyses unexpectedly found glycolytic enzymes become even more highly expressed in UOK268 cells upon FH rescue, suggesting that, at least in this model, the Warburg effect may not be completely reversible by re-introduction of FH alone.…”
Section: Discussionmentioning
confidence: 97%
“…Comparative metabolomic analyses of these different models, and the development of improved tools to assess subcellular metabolite levels should aid in the future definition of this phenomenon. [37][38] An ancillary insight from our analysis is the distinct information available from studying the consequences of FH rescue (as was done in this study) versus studying the conditions of FHdependent transformation. For example, our whole proteome analyses unexpectedly found glycolytic enzymes become even more highly expressed in UOK268 cells upon FH rescue, suggesting that, at least in this model, the Warburg effect may not be completely reversible by re-introduction of FH alone.…”
Section: Discussionmentioning
confidence: 97%
“…Because fumarate is an excellent alkene substrate and the cycloadduct is fluorescent, Meier and co-workers designed a tetrazole probe 106 to detect the oncometabolite fumarate (Scheme 25a). 47 Owing to the efficient photochemical generation of nitriles imines, this approach provides improved sensitivity compared to the previously reported hydrazonyl chloride probes. 98 Similarly, An et al developed a BODIPYlinked bithiophene-tetrazole 109 as an off-on fluorescence probe for the detection of hydrogen peroxide inside HeLa cells.…”
Section: Chemosensorsmentioning
confidence: 99%
“…Recently, Carell and co-workers exploited the hydrazonyl chlorides for bioorthogonal protein modification in aqueous media . The drawback of using hydrazonyl chloride as the nitrile imine precursor is that the hydrazonyl chloride is prone to hydrolysis in aqueous media . In contrast, tetrazoles exhibit excellent stability under aqueous conditions and provide rapid on-demand access to nitrile imines via photoirradiation.…”
Section: Tetrazole Photoclick Chemistrymentioning
confidence: 99%
“…Upon photoirradiation, the diaryl tetrazole can release N 2 and generate a nitrilimine dipole in situ, which undergoes a facile cyclization reaction with an alkene dipolarophile to afford a pyrazoline cycloadduct. The nitrilimine–alkene cycloaddition is an ultra rapid reaction and has been used in photoinduced protein labeling. Moreover, Huisgen et al also reported that the nitrilimine dipole can react with thiophenol through nucleophilic addition . Recently, several studies reported that the nitrilimine intermediate generated from UV irradiation of tetrazole can react with nearby nucleophilic groups. Inspired by these findings, we decided to develop a Ub probe containing a C-terminal tetrazole as a photocaged warhead.…”
Section: Introductionmentioning
confidence: 99%